Exertional Heat Injury: Effects of Adding Cold (4°C) Intravenous Saline to Prehospital Protocol. Issue 2 (March 2017) - Mok, Gordon; DeGroot, David; Hathaway, Nathanael E.; Bigley, Daniel P.; McGuire, Christopher S.
Abstract : This article reviews current prehospital treatment for heat casualties and introduces a retrospective study on the addition of cold (4 °C) intravenous (IV) saline to prehospital treatment and its effect on morbidity. The study is a retrospective cohort reviewing electronic medical records of 290 heat casualties admitted to Martin Army Community Hospital, Ft. Benning, GA, comparing two treatment groups; U.S. Army Training and Doctrine Command (ice-sheeting and ambient temperature IV saline) versus Benning (ice-sheeting and cold IV saline). U.S. Army Training and Doctrine Command group significantly differed from Benning group on a number of measures, the median length of stay in the hospital was 3 and 2 d, respectively ( P < 0.0001); pCr were 1.8 to 1.4 mg·dL −1, respectively (difference of 0.4 mg·dL −1 pCr, P < 0.0001). However, creatine phosphokinase, aspartate aminotransferase, and alanine aminotransferase were not significantly different across groups. Findings demonstrate that adding cold IV saline to ice-sheeting as a protocol reduces the length of hospitalization of heat casualties and lowers their peak creatinine values.